2020
DOI: 10.3389/fneur.2020.580101
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Indicators as Prognosticators in Glioblastoma Patients: A Comprehensive Meta-Analysis

Abstract: Background: Inflammation plays an important role in tumorigenesis. Previous studies have reported the prognostic value of several peripheral inflammatory markers in glioma patients, including the neutrophil-to-lymphocyte ratio (NLR). However, it still remains unclear whether inflammatory markers can independently predict the prognosis of glioblastoma (GBM) patients. The present study aims to explore the prognostic value of systemic inflammatory markers, including neutrophils, lymphocytes, platelets, the NLR, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 59 publications
(88 reference statements)
2
38
1
Order By: Relevance
“…Previous studies have shown that peripheral blood inflammatory markers are associated with the prognosis of small cell lung cancer, 28 bladder cancer, 29 hepatocellular carcinoma, 30 gastrointestinal cancers, 31 and other forms of malignancy. 32–34 Our present study also demonstrated that NLR, PLR, and LMR, were all significantly associated with rNACT. In addition, we found that a reduction in platelet count was associated with an increased risk of non-rNACT in patients with LACC.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have shown that peripheral blood inflammatory markers are associated with the prognosis of small cell lung cancer, 28 bladder cancer, 29 hepatocellular carcinoma, 30 gastrointestinal cancers, 31 and other forms of malignancy. 32–34 Our present study also demonstrated that NLR, PLR, and LMR, were all significantly associated with rNACT. In addition, we found that a reduction in platelet count was associated with an increased risk of non-rNACT in patients with LACC.…”
Section: Discussionsupporting
confidence: 81%
“…NLR has been reported to be of prognostic value for various cancers, including GB [ 8 , 9 ]. Our findings are consistent with those of several studies showing an association, in univariate analysis, of higher preoperative NLR values (cutoffs ranging from 1.7–7) with poor OS in GB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, molecular markers, such as isocitrate dehydrogenase (IDH) mutations and O 6 -methylguanine-DNA-methyltransferase (MGMT) hypermethylation are increasingly being used as predictors of prognosis and therapeutic response in GB patients [ 5 , 6 , 7 ]. There is growing evidence to suggest that preoperative hematological biomarkers, which reflect the tumor microenvironment to some extent, could be used as diagnostic and prognostic markers in several cancers, including GB [ 8 , 9 ]. For example, previous studies have indicated that neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) are associated with the clinical outcomes of GB [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that cancer cells and neutrophils work in a two-way mechanism; neutrophil-secreted cytokines help the tumor to progress while tumor cells secret chemotactic factor that can increase neutrophil count. In addition, Yang et al reported the association of elevated platelet count with worse overall survival of glioblastoma patients [ 46 ].…”
Section: Inflammationmentioning
confidence: 99%